Improving the Quality and marketing of organic fertilizer with the addition of KPDS in Sorong Regency - Pahmi, Pahmi; Rachmadana, Satria Lintang; Wijaya, Andi Ikhsan; Musaad, Ishak; Wajo , Mohamad Jen; Yuminarti, Umi; Duwith, Alfian Markus; Sentika , Muhammad Ramadhan Abdul Reja; Risnuansyah, Alsin Reza; Berepung , Elisabeth Atisa; Puspitasari , Reza Ayu (Universitas Ahmad Dahlan, 2025)
Agricultural land in Papua suffers from a deficiency of macro-nutrients essential for plant growth. This shortfall is attributed to the prevalence of utisol soil types, which make up 49.21% of the total land area. However, by implementing suitable processing technologies and innovative practices, livestock waste can be transformed into a high-value product. The innovative processing of livestock waste into fertilizer has the potential to enhance soil structure and fulfill the nutritional needs of plants. The Tunas Siaga Livestock Farmer Group and the Tunas Bangsa Youth Organization, facing challenges in the production and marketing of livestock waste products, have been identified as the target partners for this initiative. A field observation study revealed that only 20% of the total livestock waste is currently utilized for composting. The proposed solution involves using livestock waste, supplemented by natural phosphate, to improve product marketability, quality, and quantity. To achieve this goal, a comprehensive training program will be initiated, consisting of the following components: (1) training on processing livestock waste into solid and liquid organic fertilizers, enhanced by Krandalite Phosphate Deposited Soil (KPDS); (2) training in product packaging and marketing. The training program will be delivered through a combination of digital and traditional marketing channels. The effectiveness of this initiative will be assessed through a pretest and posttest administered to participants during the activities. Evaluation results indicate that the innovation involving the inclusion of KPDS in solid and liquid organic fertilizers is likely to be well-received by the target partners. Additionally, evaluation findings demonstrated that most participants experienced a significant increase in knowledge and skills in livestock waste management, with an overall improvement of 64.4%. This increase was evident in the pretest and posttest results, which showed an average score improvement among participants.